Brody Cox: capstone - Cox, Brody, artist (Colorado State University. Libraries, 2025)
The artist's statement: I have always found design to be a collaborative form of creation, and for it to be successful, it needs to solve problems. Design is like a constant ongoing conversation, and I am always learning how to listen. The clients of graphic designers require many different solutions, so being able to communicate and iterate are valuable steps in my process. The push and pull of working together is one of my favorite parts of design. To me, the best graphic work solves problems viewers didn't know they had, and to achieve that, my process shifts for each project. I also believe my execution is positively influenced by my experience in both digital design and the physical art of metalsmithing. Form can translate uniquely over two and three-dimensional spaces, and practicing in both guides the designs I create. Design is everywhere, and constantly changing, so I utilize my experiences to influence how I approach projects. Ultimately, I believe the outcomes connect the intellectual and emotional aspects of what's most important for successful work.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design